If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1 = 1 + 10x Reorder the terms: -1 + 7x = 1 + 10x Solving -1 + 7x = 1 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -1 + 7x + -10x = 1 + 10x + -10x Combine like terms: 7x + -10x = -3x -1 + -3x = 1 + 10x + -10x Combine like terms: 10x + -10x = 0 -1 + -3x = 1 + 0 -1 + -3x = 1 Add '1' to each side of the equation. -1 + 1 + -3x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 1 + 1 -3x = 1 + 1 Combine like terms: 1 + 1 = 2 -3x = 2 Divide each side by '-3'. x = -0.6666666667 Simplifying x = -0.6666666667
| 4x+4=9x+3-5x+1 | | 3xXx=30 | | 6+77x=33x+18 | | 10x+36-38x= | | 1/8(r-56)=7/8 | | -4+2x=-16+11x | | (x+2)(x-1)(x-4)= | | (x+1)(x+0)(x-2)= | | 5x+9=-57-6x | | 4(x-8)+6(5x+10)= | | 1xX^12=1.105 | | (x+5)(2x-1)(x-2)= | | sin(x)=5 | | sinx=5 | | (12x^3-7x^2+4x)-(5x^3-x^2-2)= | | 3m-n=7 | | s-10=20.01 | | 12c+8=20c-32 | | (x^2-8x+7)-(2x^2-5x-6)= | | 3x-5x=-5 | | (6x^3-x^2+11x)+(3x^3-9x+6)= | | -5v-7=10v+22 | | 15x=20-5x | | (4x^2+3x-5)+(2x+4)= | | 4/y+3=11 | | 10n+8=6n+20 | | 5x+5=5x-8 | | -5=2m+3 | | (x-1)(x+1)(x-6)= | | -16=-12 | | 9y+4=6y-4+3y | | -5=(2m+12b)3 |